Humins with Efficient Electromagnetic Wave Absorption: A By‐Product of Furfural Conversion to Isopropyl Levulinate via a Tandem Catalytic Reaction in One‐Pot. Issue 49 (22nd July 2021) - Ma, Mingwei; Liang, Na; Hou, Pan; Zhang, Peng; Cao, Jingjie; Liu, Hui; Xu, Xingliang; Yue, Huijuan; Tian, Ge; Feng, Shouhua
Abstract: Both one‐pot catalytic conversion of furfural (FAL) to isopropyl levulinate (PL) and carbonization of by‐product (humins) for electromagnetic wave absorption are discussed, which provides inspiration that humins can be applied to electromagnetic wave absorption. In the former, phosphotungstic acid (PW) is employed as a homogeneous catalyst to convert FAL to PL via a tandem reaction in one pot, with the formation of a vast amount of humins. With FAL and various intermediates as substrates, it was found that humins was a polymerization product of FAL, furfuryl alcohol (FOL) and furfuryl ester (FE) with furan rings. In addition, the in situ attenuated total reflection infrared (ATR‐IR) spectra also provided a basis for the proposed reaction route. In the latter, with the humins as raw material, P species and WO3 doped nano‐porous carbon (Humins‐700) platform formed after high‐temperature annealing is used for electromagnetic wave absorption and manifests desirable absorption performance. The minimum reflection loss (RLmin ) value is −47.3 dB at 13.0 GHz with a thickness of 2.0 mm and the effective absorption bandwidth reaches 4.5 GHz (11.2–5.7 GHz). Abstract : The by‐product (called humins) is accompanied by a one‐pot catalytic conversion reaction of furfural (FAL) to isopropyl levulinate (PL), which is carbonized (Humins‐700) and applied to a new experiment of electromagnetic wave absorption, showing superior electromagnetic wave absorption performance. The minimum reflection loss (RLmin) value is −47.3 dB at 13.0 GHz with a thickness of 2.0 mm. This provides inspiration that humins can be applied to electromagnetic wave absorption.